Treatment of bone disease after jejunoileal bypass for obesity with oral 1 alpha-hydroxyvitamin D3. Issue 8 (August 1980) - Compston, J E; Horton, L W; Laker, M F; Merrett, A L; Woodhead, J S; Gazet, J C; Pilkington, T R
Abstract : The effects of oral 1 alpha-hydroxyvitamin D3 have been investigated in 12 patients with bone disease after jejunoileal bypass for obesity. Bone histology became normal or improved greatly after four to 12 months' treatment in eight patients but showed little change or worsened in four. There was a significant rise in plasma calcium and fall in plasma alkaline phosphatase concentration with 1 alpha-hydroxyvitamin D3 therapy in the patients with a good histological response. Administration of metronidazole and cotrimoxazole to two patients who had failed to respond to 1 alpha-hydroxyvitamin D3 resulted in clinical and biochemical improvement; in one of these patients histological improvement was also documented. It is concluded that oral 1 alpha-hydroxyvitamin D3 can be effective in healing post-bypass bone disease; the failure of some patients to respond may be related to bacterial contamination of the small intestine and in those patients antibiotics may also be indicated.